Jonathan Miller : custom energy bar entrepreneur pitches sharks - Shein, James B., 1942-; Bell, Matt; Whitaker, Scott T. ([London] : SAGE, 2016)
Jonathan Miller appeared in September 2009 on 'Shark Tank', the ABC television reality show featuring entrepreneurs versus angel investors in a discussion of the business value proposition and to win a negotiation for an investment from one of the 4 Sharks. The company he founded, Element Bars, a maker of custom energy bars, needed investment capital. Prior to appearing on the show, Miller had considered several financing options available to entrepreneurs: loans and other debt capital and equity capital, each of which are evaluated in the case.
Originally Published in: Shein, J. B., Bell, M. & Whitaker, S. T. (2011). Jonathan Miller: Custom Energy Bar Entrepreneur Pitches Sharks. 5-111-003. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies; Small business -- Finance -- Case studies